Association between family management and asthma control in children with asthma. Issue 2 (11th December 2019) - Han, Li; Shangguan, Jing; Yu, Guiling; Li, Ting; Wu, Yujie; Zhou, Yunping; Liu, Panpan; Wang, Aimin
Abstract: Purpose: The purpose of this study is to investigate the association between family management and asthma control in children with asthma. Design and Methods: This cross‐sectional descriptive study recruited 142 children with asthma and their parents. We used the Family Management Measure (FaMM), the Childhood Asthma Control Test (C‐ACT), and fractional exhaled nitric oxide (FeNO) detectors to assess family management and asthma control. The McNemar's test was used to determine the proportional difference between C‐ACT and FeNO in evaluating asthma control. Pearson correlation analysis and multiple linear regression analysis were used to assess the relationship between family management and asthma control in children with asthma. Results: There was no significant difference in the proportion of C‐ACT and FeNO in evaluating asthma control (McNemar's test p  = .593). Child's Daily Life, Condition Management Ability, and Parental Mutuality were positively correlated with C‐ACT ( r  = 0.398 to 0.655; all p  < .05) and negatively correlated with FeNO ( r  = −0.245 to −0.402; all p  < .05); Condition Management Effort, Family Life Difficulty, and View of Condition Impact were negatively correlated with C‐ACT ( r  = −0.416 to −0.672; all p  < .05) and positively with FeNO ( r  = 0.248 to 0.427; all p  < 0.05). Child's Daily Life, Condition Management Effort, and View of Condition Impact dimensions significantly predicted the C‐ACT results, and the Condition Management Effort and View of Condition Impact dimensions significantly predicted the FeNO results ( p  < .05). Practical Implications: Pediatric nurses could provide family management education for parents to improve asthma control in children. In addition, pediatric nurses might assess asthma control condition of asthmatic children in combination with C‐ACT and FeNO levels.